2022
DOI: 10.1177/10776990211068408
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Fourth Estate: Asian American Journalists’ Gendered Racial Harms and Racial Activation During the COVID-19 Pandemic

Abstract: Through in-depth interviews, this study explored the voices of Asian American journalists who faced unprecedented stresses due to the racist discourse of Asian Americans as carriers of disease during the coronavirus disease 2019 (COVID-19) pandemic. Socialized to de-emphasize their vulnerabilities in their professional work, Asian American reporters generally claimed they did not experience racist harms, but further probing revealed indirect harms. Women reporters discussed internalized harms such as elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…(Dye et al, 2020, p.10). Similar findings were echoed among Chinese or Asians in France, and the US, whereby their Asian physical appearance, as well as China being the pandemic origin, were some of the reasons for feeling stigmatized and being discriminated against during the COVID-19 pandemic (Ji & Chen, 2022;Oh & Min, 2022;. Interestingly, Ji and Chen (2022) indicated that the Chinese international students not only felt stigmatized by the majority in the US, but also felt blamed and received less support from the Chinese back in China, as they were told it was their own choice and responsibility for leaving China and studying in the US.…”
Section: Miconi Et Al (2021a)mentioning
confidence: 65%
See 1 more Smart Citation
“…(Dye et al, 2020, p.10). Similar findings were echoed among Chinese or Asians in France, and the US, whereby their Asian physical appearance, as well as China being the pandemic origin, were some of the reasons for feeling stigmatized and being discriminated against during the COVID-19 pandemic (Ji & Chen, 2022;Oh & Min, 2022;. Interestingly, Ji and Chen (2022) indicated that the Chinese international students not only felt stigmatized by the majority in the US, but also felt blamed and received less support from the Chinese back in China, as they were told it was their own choice and responsibility for leaving China and studying in the US.…”
Section: Miconi Et Al (2021a)mentioning
confidence: 65%
“…Hence, during a disastrous pandemic, this could result in minority cultural groups being the scapegoats, subject to selfstigma. We found that the majority of the articles in our review pointed to Chinese or Asian Americans as the ethnic minority group who felt most stigmatized or discriminated against during the pandemic due to their behavior of wearing a mask (Ma & Zhan, 2020), their physical appearance, or their affiliation with countries in the Asian region where the pandemic was believed to have originated (e.g., Dye et al, 2020;Eichelberger, 2007;Miconi et al, 2021a, b;Molock & Parchem, 2021;Oh & Min, 2022). Moreover, other ethnic minorities, such as Persons of Color in the US, also reported higher self-stigma, potentially as the result of scapegoating (e.g., Le et al 2022;Tan & Umamaheswar, 2021).…”
Section: Culture Domains and Self-stigmamentioning
confidence: 93%